Encouraging teamwork as a project manager (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. When you're the project manager, it's up to you to make sure that plans are laid out, deadlines are met, deliverables are up to scratch, and clients are happy. But you can't do any of that alone. A project manager needs a team to lead, and it's their job to ensure that team works like a well-oiled machine. The intentions of every individual team member need to reflect your intentions if the project is to run as smoothly as possible, and that can be difficult to achieve. Everyone on the team has a different personality and has diverse work experience. There will likely be several contradictory perspectives on how the job should be done. That can result in conflicts and miscommunication, which cause barriers to progress, and projects failing to hit their deadlines or fulfill the client's expectations. Encouraging teamwork should be a priority for all project managers to keep everyone on the same wavelength, working together to achieve a common goal. Learning Objectives Learn how imperative your role is in managing conflict and keeping your team happy and on the same page when working together on a project Learn some of the things you can do to ensure your team works together well and produces high-quality work efficiently.